Cytokines, cortisol, and nitric oxide as salivary biomarkers in oral lichen planus: a systematic review - Janaina Silva Martins HUMBERTO; Jefferson Veronezi PAVANIN; Maria José Alves da ROCHA; Ana Carolina Fragoso MOTTA (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The etiopathogenesis of oral lichen planus (OLP) is still not fully elucidated, and it is believed that its development could involve a neuro-immune-endocrine profile. This systematic review investigated the relationship between cytokines, cortisol, and nitric oxide (NO) in the saliva of OLP patients. An electronic search was conducted in Pubmed/Medline, Scopus, LIVIVO, and Web of Science databases with no restriction of language to identify studies published up to December 2017. Data extraction was performed using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. A total of 140 articles were retrieved, and 32 articles fulfilled the inclusion criteria (cytokines = 17; cortisol = 9; NO = 6). The most studied cytokines in the saliva of OLP patients were interleukins IL-4, IL-6, IL-8, IFN-ү, and TNF-α, which were higher in OLP patients than in healthy controls (HC). Salivary cortisol was found to be higher in OLP than in HC in most (55.5%) of the selected studies, and all studies related to NO found higher levels of this marker in OLP than in HC. Despite controversial results, our review suggests that OLP patients have an increased inflammatory response, as indicated by the proinflammatory profile of salivary cytokines. In addition, we conclude that salivary cytokine and NO measurements may have significant diagnostic and prognostic potential for monitoring disease activity and therapeutic responses in OLP.